Inhibition of growth of U87MG human glioblastoma cells by Usnea longissima Ach. - EMSEN,BUGRAHAN (2019)
Abstract: Herbal medicines are efficient to reduce side effects in the fight against glioblastoma, which plays a critical role within brain cancer species. The recent studies designated for testing the effects of lichens that have shown numerous anticancer activities on glioblastoma so far. In the present study, different concentrations of water extract obtained from Usnea longissima Ach. were used in order to determine cytotoxic (via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and lactate dehydrogenase tests), antioxidant (via total antioxidant capacity test), pro-oxidant (via total oxidant status test) and genotoxic (via 8-hydroxy-2′-deoxyguanosine test) effects of them on human U87MG-glioblastoma cancer cell lines. Primary mixed glial-neuronal non-cancerous cells from Sprague-Dawley rats were also utilized to measure the effects of treatments on non-cancerous cells. Based on median inhibitory concentration values, the data belonged to non-cancerous cells (2486.71 mg/L) showed distinct towering compared to U87MG (80.93 mg/L) cells. The viability of non-cancerous and U87MG cells exposed to extract is decreased in a dose dependent manner. It was also showed that low concentrations of extract notably increased total antioxidant capacity on non-cancerous cells. In addition, various phenolic compounds in extract were detected through high-performance liquid chromatography. The recent results encourage that extract will be able to have therapeutic potential against glioblastoma.